Unusual false positive radioiodine uptake on 131 I whole body scintigraphy in three unrelated organs with different pathologies in patients of differentiated thyroid carcinoma: A case series - Ranade, Rohit; Pawar, Shwetal; Mahajan, Abhishek; Basu, Sandip (World Journal of Nuclear Medicine, 2016)
Three cases with unusual false positive radioiodine uptake in three different organs and pathologies (infective old fibrotic lesion in the lung, simple liver cyst, and benign breast lesion) on iodine-131 ( 131 I) whole body scintigraphy. Clinicoradiological correlation was undertaken in all three cases and the pathologies were ascertained. In all the three cases, single-photon emission computerized tomography-computed tomography (SPECT-CT) and ancillary imaging modalities were employed and were helpful in arriving at the final diagnosis.
Keywords: Differentiated thyroid carcinoma; fluorodeoxyglucose-positron emission tomography/computed tomography; radioiodine scan; iodine-131( 131 I) whole body scintigraphy